Young Women’s Opinions on the Realization of Early Adulthood Period Developmental Tasks Connected Parenthood. A Research Report - Duszyńska, Janina (Przegląd Badań Edukacyjnych (Educational Studies Review), 2016)
This article is a presentation of the results of a research whose goal was to get to know and explain the opinions of young women on the implementation of the parenting-related development tasks connected with early adulthood. The attention was focused on the views of people about a new model of fatherhood. The examination also focused on how the respondents perceive the relation between personal and professional tasks in their lives. Students of pedagogy constituted the research sample. A questionnaire form was a method of data collection. A list of parenting-related developmental tasks by R. Havighurst was the starting point for the creation of a questionnaire survey. The achieved results allowed for building of the image of a family and parenthood seen by the eyes of the respondents. The fact that the examined persons prefer a model of family based on partnership is a main conclusion from the conducted research. The respondents want to fulfill themselves both in parental as well as in professional roles. They want to share the care of children with their partners, also with reference to parental leave.